Frequency of Anemia among the Patients Presented with Myocardial Infarction at a Tertiary Care Hospital of Karachi, Pakistan - Farhan Memon Lal Chand, Rameez Ahmed, Aijaz Ali, Vashu Mal, Ghulam Rasool Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of anemia among the patients presented with myocardial infarction (MI) at a tertiary care hospital of Karachi, Pakistan. Study Design: A cross-sectional study. Place and Duration: Adult Cardiology Department of National Institute of Cardiovascular Disease (NICVD), Karachi from February 2022 to July 2022. Methodology: A total of 253 patients diagnosed with MI were included. Demographic and clinical characteristics of the patients were recorded. Hemoglobin level was obtained at the time of admission. Results: In a total of 253 patients, the mean age was 54.36±8.21 years. There were 187 (73.9%) male and 66 (26.1%) female. Frequency of anemia among the patients presented with myocardial infarction was found to be in 72 (28.5%). Frequency of anemia among patients presenting with MI was noted. Practical Implications: Anemia in myocardial infarction patients has affected the patency of vessel so this single most essentially and easily treatable component should be corrected in these patients.. Conclusion: High prevalence of anemia in patients presenting with MI was noted. Keywords: Anemia, hemoglobin, ischemic heart disease, myocardial infarction.